EFFECT OF FEED RESTRICTION AND ASCORBIC ACID SUPPLEMENTATION ON GROWTH PERFORMANCE, RECTAL TEMPERATURE AND RESPIRATORY RATE OF BROILER CHICKEN - Olukomaiya O.O; O.A. Adeyemi; O.M. Sogunle; M.O. Abioja; I.A. Ogunsola (Journal of Animal and Plant Sciences, 2015)
A total of 252 two-week old Marshall broiler chickens were used in a 4 x 3 factorial experiment to determine the effect of feed restriction and ascorbic acid supplementation on growth performance, rectal temperature and respiratory rate of broiler chickens. The birds were weighed and randomly allotted to 12 treatments with 3 replicates of 7 birds each, subjected to 4 feed restriction levels: full feeding(AD), skip a day feeding (SAD), skip two days feeding (S2D) and skip three days feeding every week (S3D) for 24 hours from 15th to 35th day of age and 3 levels of ascorbic acid supplementation (0, 150, 300 mg/kg feed). Feed was provided ad libitum from days 36 to 56. Ascorbic acid supplementation had no effect (p>0.05) on the performance parameters measured during feed restriction. Birds on S3D fed diets containing 300 mg/kg ascorbic acid had the highest (p<0.05) weight gain during realimentation. Ascorbic acid lowered the rectal temperature in birds on S2D and S3D at the end of feed restriction. At the end of realimentation, birds on S3D fed diets containing 150 mg/kg ascorbic acid had the lowest (p<0.05) respiratory rate. Ascorbic acid supplementation at 150 mg/kg feed enhanced weight gain, rectal temperature and respiratory rate of broiler chickens on skip three days feeding every week.
Keywords: Feed restriction; Ascorbic acid; Broiler performance; Rectal temperature; Respiratory rate